Hydrochemical Evolution and Nitrogen Behaviors in Coastal Groundwater Suffered From Seawater Intrusion and Anthropogenic Inputs - Dun, Yu; Ling, Junhong; Wang, Rui; Wei, Jun; Zhou, Qianyi; Cao, Yingjie; Zhang, Yizhang; Xuan, Yingxue (Frontiers in Marine Science, 2022)
Coastal aquifers play key roles in providing freshwater resources to maintain the social and economic development in coastal areas. However, climate change and human activities have dramatically affected the quantities and qualities of groundwater in coastal aquifers. In this study, stoichiometric analysis of hydrogeochemistry, multivariate analysis, and isotopic trancing techniques were used to reveal the local hydrochemistry characteristics, the natural and anthropogenic origins, and the major hydrochemical evolution in a typical coastal aquifer located in the Pearl River estuary. According to hydrogeological conditions and groundwater burial conditions, the aquifer was divided into three zones, namely, semiconfined fissure groundwater (SFGW), recharged fissure groundwater (RFGW), and porous medium groundwater (PGW). Seawater intrusion, ion exchange, water–rock reaction, and human activities were the main controlling factors affecting the characteristics of groundwater, but there were significant differences in the main controlling effects of different zones. Among them, the samples from the SFGW was severely affected by seawater intrusion, and the contributions of seawater ranged from 6% to 97%. Obvious cation exchange process occurred during the seawater intrusion. The hydrochemical characteristics of the PGW and the RFGW were mainly controlled by water–rock interaction. In addition, human activities had further influence on the hydrochemical characteristics of groundwater, which resulted in elevated nitrate–nitrogen (NO3−–N). The mean NO3–N concentrations in the PGW and the SFGW were 6.58 and 3.07 mg/L, respectively. Furthermore, the δ15N–NO3− and δ18O–NO3− values in these two regions ranged from +2.35‰ to +27.54‰ and from +0.39‰ to +18.95‰, respectively, indicating that the anthropogenic input contributed to the increased nitrate. Redox analysis and dual nitrogen isotopic evidence indicated that denitrification was the predominant biogeochemical process in the PGW and the RFGW. This study highlights the impacts of seawater intrusion and anthropogenic inputs on hydrochemical evolution and nitrogen behaviors in coastal groundwater, which provides a scientific basis for the management of groundwater resources in coastal aquifers.